Nutrition of black pepper (Piper nigrum L.) - a Brazilian experience - Partelli, Fábio Luiz (Journal of Spices and Aromatic Crops, 2009)
Despite investment risk and price variations, among other difficulties, Brazilian farmers arestill investing in black pepper (Piper nigrum) cultivation due to relative price increment overthe years. Action has already been implemented, on improvement of cultivars and diagnosis,fertilization and irrigation, based on technical information for increasing the productivity ofthe crop. Adequate nutritional diagnosis, based on a proper sample method and regionalpatterns, will result in efficient input recommendation with a consequent improvement inproduction with higher sustainability. The DRIS (Diagnosis and Recommendation IntegratedSystem) has been extensively used in Brazil, which contributes to efficient nutrition diagnosisand fertilizer recommendation. The use of simple cultural procedures such as use of covercrops and organic fertilization, among others, has a great potential to control weeds, improvesoil quality and mineral nutrition in black pepper, contributing to sustainable production.This review includes information on research work being undertaken in Brazil, on blackpepper nutrition (nutrient extraction, foliar patterns, nutritional diagnosis and fertilizerrecommendations), including fertilization and diagnosis strategies for increasing theproductivity of the crop.